Inovasi dan Ketekunan sebagai Kunci Keberhasilan Pengusaha Muda di Bisnis Ayam KFC: Studi Kasus Usaha Fried Chicken Smile di Kecamatan Medan Tembung - Mazaya Khalda Fachri Berutu; M. Luthfi Lubis; Mhd. Aldri Syahputra; Zainarti Zainarti (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study explores the roles of innovation and perseverance as critical success factors for young entrepreneurs in the fried chicken business through an in-depth case study of Fried Chicken Smile, located in Medan Tembung Subdistrict. The research focuses on how young entrepreneurs are able to survive and grow in a highly competitive culinary market dominated by global brands such as KFC. Using a qualitative research approach, data were collected through in-depth interviews with business owners and employees, direct field observations, and documentation analysis. The study is supported by several theoretical perspectives, including Grit Theory, which emphasizes perseverance and passion for long-term goals; Entrepreneurial Behavior Theory, which explains proactive and adaptive business behavior; and Schumpeter’s Innovation Theory, which highlights innovation as a driver of competitive advantage. The findings indicate that business success is influenced by continuous product innovation, particularly through adapting menu flavors to local tastes, maintaining consistent operational quality, and implementing effective digital marketing strategies via social media platforms. In addition, strong social support from family, peers, and local communities plays a significant role in sustaining entrepreneurial motivation. Overall, the study demonstrates that the combination of innovation, persistence, and social capital enhances competitiveness and supports the growth of micro, small, and medium enterprises (MSMEs). These findings provide valuable insights for the development of young entrepreneurship in Indonesia’s dynamic culinary sector.